Safety-Based Dolphin Tourism Supports Tourism Development - Werang, Basilius Redan; Anak Agung Gede Agung; Alexander Hamonangan Simamora; I Gusti Ngurah Agung Suryaputra (International Journal of Community Service Learning, 2024)
Dolphin tourism is one of the famous tourist attractions and is a characteristic of Lovina Beach. this activity can potentially be a source of income for the local community. This dolphin tour is very popular with domestic and foreign tourists, and not a few capture moments during dolphin tours; this triggers tourists to pay less attention to safety during dolphin tours. This community service aims to improve security services (safety guards) in guiding tourists and to improve digital-based dolphin tourism information service facilities. The method applied is training and community service; the subject of the study was the Segara Wangi group, with a total of 30 members. The results of the training and community service showed a significant increase in the average ability of participants after participating in the training. The results of the data analysis showed that the implemented community service program was successful in increasing the knowledge and skills of participants related to marine tourism security management and Dolphin Tourism WEB Booking management.